RECONSTRUCTING RACISM: TRANSFORMING RACIAL HIERARCHY FROM "NECESSARY EVIL" INTO "POSITIVE GOOD". Issue 1 (14th June 2017) - Grynaviski, Jeffrey D.; Munger, Michael C.
Abstract: Our theoretical claim is that racism was consciously (though perhaps not intentionally) devised, and later evolved, to serve two conflicting purposes. First, racism served a legal-economic purpose, legitimating ownership and savage treatment of slaves by southern whites, preserving the value of property rights in labor. Second, racism allowed slave owners to justify, to themselves and to outsiders, how a morally "good" person could own slaves. Racism portrayed African slaves as being less than human (and therefore requiring care, as a positive duty of the slave owner, as a man cares for his children, who cannot care for themselves), or else as being other than human (and therefore being spiritually no different from cattle or horses, and therefore requiring only the same considerations for maintenance and husbandry). The interest of the historical narrative presented here is the emergence of racial chattel slavery as a coherent and fiercely defended ideal, rather than the "necessary evil" that had been the perspective of the Founders. The reason that this is important is that the ideology of racism persisted far beyond the destruction of the institution of slavery, through Reconstruction, Jim Crow, and in some ways persisting even today. This work is an example of the problems of assuming that there is a "feedback" mechanism by which moral intuitions are updated and perfected; to the contrary, as suggested by Douglass North, even socially inferior ideologies can prove extremely persistent.